Discrete fracture network modelling reconstructs fracture array evolution and related petrophysical properties over geological time - Matthew S. Hodge; Mark Cottrell; Jochen Knies; Giulio Viola (Communications Earth & Environment)
Abstract Fractured rock petrophysical studies rarely use temporal constraints, thus hindering fracture-related permeability and connectivity estimation during past geofluid migration. Here we present a conceptual approach, using a stochastic method incorporating absolute ages to reconstruct fracture arrays back in geological time. Generating ‘grown’ discrete fracture network models, we simulate the hydraulic behaviour of fractured rock volumes from the late-Cretaceous/Palaeocene to the Devonian, via progressive fracture back-stripping. We reveal that for the examined rock mass, maximum principal permeability increased through time from 9.47e-14 m2 to 4.44e-13 m2 (~3 orders of magnitude) along with the maximum horizontal permeability orientation shifting from NE-SW to NW-SE. Similarly, the connectivity metric increased with fracture saturation, peaking in the mid-Cretaceous. For comparison, dated offshore hydrocarbon secondary migration potentially coincides with our results. Back-stripping of time-constrained fracture sets is therefore a powerful method to investigate and quantify the dynamic evolution of petrophysical properties through geological time.